3D printed continuous fiber reinforced composite lightweight structures: A review and outlook. (1st February 2023) - Cheng, Ping; Peng, Yong; Li, Shixian; Rao, Yanni; Le Duigou, Antoine; Wang, Kui; Ahzi, Said
Abstract: Continuous fiber reinforced composite lightweight structures (CFRSs) are widely applied to aerospace, automobile, marine and other fields due to their high specific strength and modulus, low density and fatigue resistance. Innovations in the additive manufacturing technique of continuous fiber reinforced composites (CFRC) opened new perspectives for the integrated design and fabrication of composite lightweight structures with customized performance and acceptable cost. This paper reviewed the state-of-the-art 3D printing CFRSs and elaborated their future perspectives and potential applications. Specifically, different existing CFRSs printing techniques were reviewed, and the limitations of current processing methods were discussed in details. Then, the CFRSs including 2D and 3D types were discussed in terms of path planning, structural design and optimization methods. Further, the mechanical properties and novel applications in shape morphing and self-monitoring of CFRSs were presented. Finally, this paper concluded with an outlook on future research opportunities on 3D printing CFRSs from design, fabrication to final applications.